The world is changing... (Encuentros, 2020)
They know it very well, they see it everywhere, they read it and they feel it, there is no way that I did not stop talking about it, covid-19, a virus that keeps the world on edge, and, despite that, being Human continues its march towards other social dimensions (Espinosa, 2020).